Electroreduction of benznidazole in dimethylsulfoxide - Arguelho, MLPM; Silva, G. M.; Stradiotto, Nelson Ramos [UNESP] (Electrochemical Soc Inc, 2001)
The electrochemical behavior of benznidazole has been investigated in dimethylsulfoxide by cyclic voltammetry and controlled-potential electrolysis. The reduction occurs in two one-electron steps, where the first electron transfer corresponds to the reversible formation of the radical anion followed by a slow chemical reaction. The second electron transfer is attributed to the reduction of the radical anion to a dianion by an electrodic process involving a Very fast cleavage of the dianion with the formation of a lactam derivative as the principal product of reduction in aprotic medium. (C) 2001 the Electrochemical Society. All rights reserved.